Effects of edge cracks on the dynamics of piezoelectric cantilever based MEMS sensor - Shoaib, M. (Institute of Electrical and Electronics Engineers Inc., 2017)
This paper presents edge crack fault modeling for piezoelectric cantilever based MEMS sensor using LTI (linear time invariant) technique. Frequency fault model is developed to analyze the dynamic behavior of the device in term of displacement, frequency and output electrical response. First an analytical model is developed that shows the electromechanical coupling of the device. Crack function along with the dynamic mass is used to develop the resonance frequency of cracked cantilever. Then LTI model of faulty device is developed by integrating the analytical equations using Simulink tool. The LTI model is validated by comparing its results with the FEM design using same design parameters using COMSOL tool. The results shows that resonance frequency of the device is changed by changing the crack size and its location in the cantilever structure. © 2016 IEEE.